Spouse Employment Status, Age, Cadre and Religiosity as Predictors of Wife Abuse among Officers and Men of Nigerian Police Force - Onuoha, Uchenna (2014)
Interest at curbing domestic violence may have been motivated by its negative effects on the productivity of victims of abuse. Despite concerted global efforts at curbing domestic violence, gaps still exist in the scholarly literature on the influence of personal characteristics on domestic violence. The present study extended previous domestic violence literature by examining the relationship between demographic factors and wife abuse among policemen in the Nigerian Police Force. Participants consisted of 212 officers and men of the Nigerian Police Force, purposively selected for the study. The sample for this study was made up of 88 officers and 144 non-commissioned officers. Respondents’ age ranged from 28 to 57 years. 143 participants had wives who were employed, while the remainder (69) had unemployed wives. Educational qualification distribution showed that 60 participants possessed senior secondary school certificate, 66 had Ordinary National Diploma, while the remaining 86 had university degrees and postgraduate certificates. Following a critical review of domestic violence literature, three hypotheses were generated and tested using t-test for independent measure and multiple regression analysis. Results indicated significant influence of spouse employment status on wife abuse (<.01), such that participants with employed spouse reported lower on wife abuse than participants with unemployed spouse. Both age and religiosity had significant prediction on wife abuse (<.05). However, there was no significant influence of participants’ cadre on wife abuse (>.05). Empowering women to increase their earning power and reduce domestic violence was recommended among others. Keywords: Wife Abuse, Age, Religiosity, Cadre, Nigeria Police Forc